2013
DOI: 10.1111/1750-3841.12223
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Suppresses Intracellular ROS Formation, MMP Activation, and Cell Motility in Human Fibrosarcoma Cells

Abstract: Cell metastasis is a major cause of death from cancer and can arise from excessive levels of oxidative stress. The objective of this study was to investigate whether the natural flavonoid quercetin can inhibit matrix metalloproteinase (MMP)-2 and -9 activities through the attenuation of reactive oxygen species (ROS) formation, an event expected to lead to the inhibition of cell motility. To induce sustained ROS formation, cells were treated with phenazine methosulfate (PMS; 1 μM). Noncytotoxic concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 26 publications
1
23
1
Order By: Relevance
“…Although suppression of MMP-9 expression by kaempferol, quercetin, and morin was reported in different conditions Lee et al, 2013;Lin et al, 2010;Sivaramakrishnan and Niranjali Devaraj, 2009;Yi et al, 2012), our study showed that MMP-9 secretion from HT-1080 cells was severely decreased by galangin as well as kaempferol, and moderately decreased by fisetin. Interestingly, quercetin weakly affected and morin did not affect MMP-9 secretion.…”
Section: Discussioncontrasting
confidence: 57%
“…Although suppression of MMP-9 expression by kaempferol, quercetin, and morin was reported in different conditions Lee et al, 2013;Lin et al, 2010;Sivaramakrishnan and Niranjali Devaraj, 2009;Yi et al, 2012), our study showed that MMP-9 secretion from HT-1080 cells was severely decreased by galangin as well as kaempferol, and moderately decreased by fisetin. Interestingly, quercetin weakly affected and morin did not affect MMP-9 secretion.…”
Section: Discussioncontrasting
confidence: 57%
“…These events may be triggered by ROS and can be reduced by antioxidants, such as quercetin (Lee et al, 2013). Moreover, gradual oxidative damage during life to DNA bases in genes coding for the dermal matrix components collagen and elastin leads to their reduced expression in aged skin (Uitto, 1979).…”
Section: Intrinsic Agingmentioning
confidence: 99%
“…More specifically, studies have shown that quercetin has the capacity to decrease MMP-2 and -9 expression that have a proeminent effect on cancer cell invasion and metastization [3,[58][59][60][61][62][63][64]. In this context, in 2004 Zhang and colleagues [60] had demonstrated that quercetin is capable of reducing the invasive potential of a melanoma cell line by decreasing pro-MMP-9 through PKC pathway [60].…”
Section: Quercetin Effect On Cell Invasionmentioning
confidence: 99%